2004
DOI: 10.1038/sj.npp.1300440
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Phosphodiesterase 4 (PDE4) Enzyme Reverses Memory Deficits Produced by Infusion of the MEK Inhibitor U0126 into the CA1 Subregion of the Rat Hippocampus

Abstract: Cyclic AMP-specific phosphodiesterase 4 (PDE4), which is an integral component of NMDA receptor-mediated cAMP signaling, is involved in the mediation of memory processes. Given that NMDA receptors also mediate MEK/mitogen-activated protein kinase (MAPK, ERK) signaling, which is involved in synaptic plasticity, and that some PDE4 subtypes are phosphorylated and regulated by ERK, it was of interest to determine if PDE4 is involved in MEK/ERK signaling-mediated memory. It was found that rolipram, a PDE4-selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 37 publications
2
83
0
Order By: Relevance
“…While overall inhibition of PDE4 enhances memory performance in animals (Barad et al, 1998;Zhang et al, 2004Zhang et al, , 2005, PDE4BÀ/À mice did not show significant changes in either short-or long-term memory in step-down passive avoidance and Morris water-maze tasks (Table 1 and Figure 5), two tests measuring hippocampus-based memory (Bevilaqua et al, 1997). This is consistent with the limited expression of PDE4B in the hippocampus (Cherry and Davis, 1999).…”
Section: Pde4b-deficiency and Behavior H-t Zhang Et Alsupporting
confidence: 75%
See 2 more Smart Citations
“…While overall inhibition of PDE4 enhances memory performance in animals (Barad et al, 1998;Zhang et al, 2004Zhang et al, , 2005, PDE4BÀ/À mice did not show significant changes in either short-or long-term memory in step-down passive avoidance and Morris water-maze tasks (Table 1 and Figure 5), two tests measuring hippocampus-based memory (Bevilaqua et al, 1997). This is consistent with the limited expression of PDE4B in the hippocampus (Cherry and Davis, 1999).…”
Section: Pde4b-deficiency and Behavior H-t Zhang Et Alsupporting
confidence: 75%
“…It is well established that PDE4 inhibitors such as rolipram produce antidepressant-like and memory-enhancing effects (Barad et al, 1998;O'Donnell and Zhang, 2004;Zhang et al, 2004Zhang et al, , 2006Zhang and O'Donnell, 2007). They also may induce anxiogenic-like effects and sedation (Heaslip and Evans, 1995;Imaizumi et al, 1994;Silvestre et al, 1999b), although an anxiolytic-like effect also has been reported (Silvestre et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDE4 is a cAMP-specific PDE that is prevalent in the brain and is the target of antidepressant and cognitive enhancing pharmacotherapeutics. With activity being regulated by both cAMP and extracellular signal-regulated kinase (ERK) signaling, PDE4 is a key component in NMDAmediated memory processes (Zhang, Zhao et al 2004). The PDE4 subfamilies PDE4A, PDE4B, PDE4C, and PDE4D are highly expressed in human brain regions, whereas rat brain primarily expresses PDE4A, B, and D (Cherry and Davis 1999;Takahashi, Terwilliger et al 1999;Fujita, Zoghbi et al 2005;Parker, Matthews et al 2005).…”
Section: Cyclic Amp Cascadementioning
confidence: 99%
“…PDE-4 inhibition could, thus, be associated with a complementary upstream mechanism that recruits adenylyl cyclase: for example, ␤-AR, 5-HT 4 , or 5-HT 6 receptor agonism. 113,117,118,231,232 Such a dual-acting drug should mainly inhibit PDE-4 (and hence favor cAMP generation) in structures where ␤-AR, 5-HT 4 or 5-HT 6 receptors are stimulated. This would increase the therapeutic window and enhance both the efficacy and duration of agonist-mediated actions.…”
Section: Strategies For the Future? Multifunctional Agents Interactinmentioning
confidence: 99%